(untitled) (Baghdad Science Journal, 2014)
Background: Osteoporosis (OP) is a systemic disease characterized by low bone mass and micro architectural deterioration of bone tissue, resulting in an increased risk of fractures and has touched rampant proportions. Osteocalcin, one of the osteoblast-specific proteins, showed that its functions as a hormone improves glucose metabolism and reduces fat mass ratio. This study is aimed to estimate the osteocalcin and glucose level in blood serum of osteoporotic postmenopausal Women with and without Type 2 Diabetes.Materials and methods: 60 postmenopausal women with osteoporosis divided into two groups depending on with or without T2DM, 30 patients for each. Serum samples of 30 healthy postmenopausal women were collected as control group. Osteocalcin was measured by ELISA method using a kit of (CUSABIO. China). Glucose was determined by spectrophotometric method. Results: Mean serum osteocalcin in postmenopausal osteoporotic women without Type II Diabetes is higher than control group and the group with T2DM (p ? 0.001). Conclusion: Bone formation marker increases at postmenopausal osteoporosis women; Hyperglycemia also induces osteoblast function and reduces of production osteocalcin at T2DM.